THE INFLUENCE OF SPEECH GENRES ON THE FORMATION OF LINGUISTIC PERSONALITY IN SHORT STORIES - Bazarova Ziyoda Eshbaevna (European International Journal of Pedagogics, 2023)
The article is devoted to the influence of speech genres in short stories on the formation of linguistic personality. The article examines the structure of the speech genre, presents the typology of speech genres in short stories from a linguistic point of view, considers the concept of "linguistic personality" and determines its place in the literary text. The author also researches and determines the connection between speech genres and the language personality of the hero of the work of art. The article also focuses on the interaction of speech genres shown in short stories and explains the principles of their coexistence.